Reviews about the Effectiveness of Marketing Strategies and Performance Marketing in the City of Sanandaj Banks - Afzal, AbdolRahman Maleki; SoltanPanah, Heirsh (Journal of History Culture and Art Research, 2017)
The purpose of this research is to review the relationship between effectiveness of marketing strategies performance Marketing Bank branches in the city of Sanandaj. This research in terms of purpose is applied; and also in terms of method is descriptive correlational research and in term of duration is a single period. The statistical population contains staff at the branch of the bank of Sanandaj city. To choose the statistical sample by using classical random sampling and according to the statistical formula, a sample of 302 people is selected from among the statistical population. According to research methodology and the type of the underlying data in this study, questionnaire of standard marketing strategies and researcher marketing performance are used as the main tool to measure and data collection. In order to do the statistical analysis, SPSS statistical analysis software is used. The findings show that there is a significant positive relationship between the effectiveness of marketing strategies and Performance Marketing Banks city of Sanandaj. Also, the results show that between all of the components of the effectiveness of marketing strategies and Performance Marketing (customer-philosophy (0.611), Integrated Marketing Effort (0.562), Marketing Information (0.361), Strategic orientation (0.573), Orientation Efficiency (0.678) there is a significant relationship.